2007
DOI: 10.1185/030079907x210615
|View full text |Cite
|
Sign up to set email alerts
|

Cost of care for patients with rheumatoid arthritis receiving TNF-antagonist therapy using claims data

Abstract: Annual healthcare cost for adalimumab patients was significantly less than for infliximab patients and was comparable to etanercept patients. This analysis is subject to the usual limitation of claims data analyses in that few clinical details are available and causal inference conclusions are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 7 publications
8
27
0
Order By: Relevance
“…In addition, a study of the USA population showed similar data (10). The two papers showed that the annual healthcare cost was significantly less than for infliximab patients.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, a study of the USA population showed similar data (10). The two papers showed that the annual healthcare cost was significantly less than for infliximab patients.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, this analysis complements previous analyses that also reported that the cost of etanercept was the lowest of the TNF blockers among patients with rheumatoid arthritis. [17][18][19][20][21] In this analysis, estimates of total annual costs of TNFblocker treatment included the costs of both the index TNF blocker and the nonindex TNF blockers among patients who switched treatment in the first year after the index date. The intent was to provide a real-world estimate of the total annual cost of TNF-blocker treatment.…”
Section: Limitationsmentioning
confidence: 99%
“…Wu and colleagues conducted a national database study to compare the cost of care with adalimumab, infliximab and etanercept for 1 year (beginning 1 January 2003) in privately insured patients with RA [79]. Healthcare utilization and costs were assessed for both non-RA-and RA-related medical costs.…”
Section: Cost-of-care Studiesmentioning
confidence: 99%